2016
DOI: 10.1152/ajprenal.00088.2016
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular epithelial cell prorenin receptor regulates blood pressure and sodium transport

Abstract: The physiological significance of the renal tubular prorenin receptor (PRR) has been difficult to elucidate due to developmental abnormalities associated with global or renal-specific PRR knockout (KO). We recently developed an inducible renal tubule-wide PRR KO using the Pax8/LC1 transgenes and demonstrated that disruption of renal tubular PRR at 1 mo of age caused no renal histological abnormalities. Here, we examined the role of renal tubular PRR in blood pressure (BP) regulation and Na(+) excretion and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 49 publications
2
62
0
Order By: Relevance
“…In agreement with this finding, Ramkumar et al observed a similar stimulatory effect of prorenin on ENaC activity in isolated split-open CD 32 . Moreover, the prorenin effect was similarly unaffected by AT1 blockade 32 . Besides the ENaC regulation at activity level, PRR also upregulates α-ENaC mRNA expression in mIMCD3 cells exposed to low salt media or AngII through serine/threonine-protein kinase-1 and phosphorylated Nedd4-2 {also known as Nedd4L (neural precursor cell-expressed developmentally downregulated gene 4-like)} 33 .…”
Section: Prr Regulation Of Na+ Homeostasissupporting
confidence: 71%
See 2 more Smart Citations
“…In agreement with this finding, Ramkumar et al observed a similar stimulatory effect of prorenin on ENaC activity in isolated split-open CD 32 . Moreover, the prorenin effect was similarly unaffected by AT1 blockade 32 . Besides the ENaC regulation at activity level, PRR also upregulates α-ENaC mRNA expression in mIMCD3 cells exposed to low salt media or AngII through serine/threonine-protein kinase-1 and phosphorylated Nedd4-2 {also known as Nedd4L (neural precursor cell-expressed developmentally downregulated gene 4-like)} 33 .…”
Section: Prr Regulation Of Na+ Homeostasissupporting
confidence: 71%
“…These results suggest that prorenin via PRR induces Nox4-derived ROS resulting in a direct activation of ENaC. In agreement with this finding, Ramkumar et al observed a similar stimulatory effect of prorenin on ENaC activity in isolated split-open CD 32 . Moreover, the prorenin effect was similarly unaffected by AT1 blockade 32 .…”
Section: Prr Regulation Of Na+ Homeostasissupporting
confidence: 70%
See 1 more Smart Citation
“…Emerging evidence supports an important role of renal PRR in regulation of intrarenal renin-angiotensin-system (RAS) and renal function 2931 . On the other hand, previous studies have documented interaction between fructose metabolism and the RAS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sPRR may act independent of Ang II/Ang II receptors to induce expression and activity of the epithelial sodium channel (ENaC) in the CD, thus contributing to an increase in blood pressure via enhanced Na + reabsorption in the CD (Ramkumar et al. ).…”
Section: Discussionmentioning
confidence: 99%